D-distance Magic Labeling on Some Class of Graphs - P, Shankaran; K, Chaithra (International Journal of Engineering and Technology, 2018)
In this paper we study  -distance magic labeling on path with n vertices, D-distance magic labeling on trees when D= (0,1) and D=(d) where d is a  diameter of tree and (0,1)-distance magic labeling of complete graph..